2013
DOI: 10.1002/cctc.201300742
|View full text |Cite
|
Sign up to set email alerts
|

Silanol‐Assisted Aldol Condensation on Aminated Silica: Understanding the Arrangement of Functional Groups

Abstract: Free silanol groups are known to promote the activity of aminated silica. In this work the effect of the silanol‐to‐amine ratio on the aldol condensation of 4‐nitrobenzaldehyde and acetone is investigated in a range from 0 to 2.4. Irrespective of the amine density, identical, moderate turnover frequencies are obtained if the silica exclusively has amines on its surface. The turnover frequency increases with increasing silanol‐to‐amine ratio until an upper limit is reached at a silanol‐to‐amine ratio of 1.7. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 59 publications
9
89
0
Order By: Relevance
“…The promoting effect of the silanol groups and the arrangement of active sites. The data reported in Table 3 clearly show how the activity exhibited by amine groups is enhanced by the presence of silanols, which confirms the cooperativity between the acid and base sites [27,28,58]. The product distribution is not significantly affected by the presence of silanol groups, however.…”
Section: Catalyst Propertiessupporting
confidence: 62%
See 2 more Smart Citations
“…The promoting effect of the silanol groups and the arrangement of active sites. The data reported in Table 3 clearly show how the activity exhibited by amine groups is enhanced by the presence of silanols, which confirms the cooperativity between the acid and base sites [27,28,58]. The product distribution is not significantly affected by the presence of silanol groups, however.…”
Section: Catalyst Propertiessupporting
confidence: 62%
“…Recently we showed that the cooperativity does not only depend on the ratio of both types of active sites but also on the arrangement of these active sites on the catalyst surface [58]. Thermodynamic calculations for a n-propylamine-toluene mixture revealed positive deviations from ideal liquid behaviour, i.e., propylamine-propylamine interactions preferentially occur as compared to propylamine-toluene interactions.…”
Section: Catalyst Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Pluronic P123 block copolymer (EO 20 All SBA-15 materials were prepared according to previous reports [18,19,37,[49][50][51][52][53][54][55]. The details of the synthetic procedures are in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The facile ability to separate and recycle heterogeneous catalysts from reactive fluids makes them attractive targets for incorporating acid-base cooperativity in new materials. While the results from homogeneous catalysts can be used as a basis for designing heterogeneous catalysts, incorporating cooperative catalytic elements is considerably more challenging in heterogeneous systems such as those based on silica supports because the silanols present on the surface, which act as organic functional group anchoring points or as weakly acidic cooperative partners, are typically not uniformly distributed [20][21][22][23][24][25][26]. Despite the complexity of silica-based catalysts, numerous studies demonstrate the ability to design materials that exhibit cooperative interactions, providing considerable insights into optimizing such catalysts.…”
Section: Introductionmentioning
confidence: 99%